PREDICTION THE SHEAR STRENGTH AND SHEAR MODULUS OF SAND-CLAY MIXTURE USING BENDER ELEMENT - Alshameri, Badee (Journal of Applied Engineering Science, 2022)
Employing the conventional laboratory geotechnical methods such as shear box test to measure shear strength and shear modulus require destroying the samples which is seen as time consuming and costly. Whilst the bender element technique (BE) maintains the sample condition, time, and cost efficiency. The aim of this research was to develop new empirical correlation equations and improve the prediction of the shear modulus (τ) and shear strength (G) using the maximum shear modulus (Gmax) from the bender element technique and combination of the index soil properties. Several sand-clay mixtures were compacted and subjected to bender element test as well as sheared using shear box test to measure both geotechnical and dynamic parameters. The results showed the critical stage at fine-grained (FG) equal to 50% where any further increment beyond this value led to decrement the soil mixture strength. Both τ and G were normalized using moisture content, unit weight (density), and applied normal stress. The empirical equations from the normalized shear strength τN were applied on the previous field data to exam their reliable and limitations. The geotechnical factors in the normalized data play significant effect on the application of these empirical equations. Among the five empirical equations tested, only two equations indicate significant validity and reliability to predict the shear strength. Finally, the 5m depth limit was recommended to apply the equation consistently
Keywords: sand-clay mixture, bender element, shear modulus, shear strength, maximum shear modulus